Anisotropic, rate-dependent ductile fracture of Ti-6Al-4V alloy. (March 2022) - Ruiz de Sotto, Miguel; Doquet, Véronique; Longère, Patrice; Papasidero, Jessica
An extensive experimental campaign was run to investigate the influence of the loading direction, stress state (triaxiality ratio ranging from −0.5 to 1), and strain rate (from 10 −3 to 1.5x10 3 s −1 ) on the ductile fracture of Ti-6Al-4V titanium alloy. Microscopic and macroscopic observations provided some insight into the shear-driven or micro-voiding-controlled damage mechanisms prevailing at low and high triaxiality ratios, respectively. Numerical simulations were run to determine the local loading paths to fracture in terms of plastic strain as a function of stress triaxiality ratio and Lode parameter. The ductility was found to be anisotropic, but only weakly dependent on the strain rate in the considered range. The anisotropy in ductility was different in tension (maximum along DD) and in compression (maximum along ND). The fracture strain decreased with the absolute value of the triaxiality, with a maximum close to zero. No clear correlation with the Lode parameter was found.